The Intersection of Politics and Sports: Examining the Role of the Government in Shaping Sports Justice in Indonesia (Indonesian Sports Justice Review, 2024)
In Indonesia, sports have long been intertwined with political agendas, influencing both public policy and the broader societal landscape. This paper explores the role of the government in shaping sports justice, particularly how political decisions affect equity, resource allocation, and opportunities for athletes. Through an analysis of government involvement in national sports programs, infrastructure development, and the regulation of sports bodies, the paper investigates the ways in which political motivations and power dynamics shape sports access and outcomes. It examines case studies of both positive and negative impacts, such as the distribution of funding, representation of ethnic and regional groups, and the politicization of elite sports programs. The study concludes by proposing recommendations for a more just and equitable sports system, with a focus on transparency, accountability, and the separation of sports from political exploitation.